2016
DOI: 10.3233/jad-160812
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Degeneration of Dementia-Related Subcortical Structures Throughout the Lifespan

Abstract: Age-related changes in brain structure are a question of interest to a broad field of research. Structural decline has been consistently, but not unambiguously, linked to functional consequences, including cognitive impairment and dementia. One of the areas considered of crucial importance throughout this process is the medial temporal lobe, and primarily the hippocampal region. Gender also has a considerable effect on volume deterioration of subcortical grey matter (GM) structures, such as the hippocampus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 164 publications
0
11
0
Order By: Relevance
“…In addition, anesthesia/surgery may induce microglial activation, resulting in the release of inflammatory factors, such as tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1β, and IL-6 [11,12]. Furthermore, the hippocampal CA1 region is critical for cognition [13], and overactivated microglia and neuroinflammation create a neurotoxic response and cause synaptic dysfunction, resulting in cognitive dysfunction [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, anesthesia/surgery may induce microglial activation, resulting in the release of inflammatory factors, such as tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1β, and IL-6 [11,12]. Furthermore, the hippocampal CA1 region is critical for cognition [13], and overactivated microglia and neuroinflammation create a neurotoxic response and cause synaptic dysfunction, resulting in cognitive dysfunction [14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in treatments of chronic diseases related to old age, dementia is considered one of the most significant public health challenges (Nemeth et al, 2017). It is estimated that 74.7 million people around the world will be living with dementia by the year 2030 (Alzheimer's Disease International., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Two-thirds of Americans living with AD dementia are women, and neither their longer lifespans nor differences in lifestyle compared to men can explain these numbers. It has been suggested that the higher frequency of female AD morbidity is caused by increased chances of AD initiation earlier in life due to menopause [ 111 , 112 ], although the mechanisms underlying this phenomenon are not clear. The proposed hypothesis explains these sex differences by changes in the spectrum of secreted PG miRNA hormones from pro-developmental to anti-carcinogenic, changes that are associated with decreased levels of estrogen.…”
Section: Introductionmentioning
confidence: 99%